2014
DOI: 10.1155/2014/258402
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Extraction and Enrichment of Steroidal Alkaloids from Bulbs of CultivatedFritillaria cirrhosa

Abstract: The bulbs of cultivated Fritillaria cirrhosa (BCFC) are used in China both for food and folk medicine due to its powerful biological activities. The aim of this study is to optimize the extraction and enrichment conditions of alkaloids from BCFC. Firstly, the orthogonal experimental design was used to optimize and evaluate four variables (ethanol concentration, solid-liquid ratio, extraction time, and temperature). Thereafter, resin adsorption was as a means to enrich alkaloids. Among 16 tested resins, H-103 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 27 publications
(48 reference statements)
0
11
0
Order By: Relevance
“…Because production of BFC obtained from the wild field has fallen short of consumption and the price is growing higher in recent decades, the artificial cultivation of BFC has been gradually developed by the traditional Chinese medicinal cultivation companies (Wang et al, 2014a ). In this work, we investigated six artificial cultivated bases and two individual cultivated plantations (Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because production of BFC obtained from the wild field has fallen short of consumption and the price is growing higher in recent decades, the artificial cultivation of BFC has been gradually developed by the traditional Chinese medicinal cultivation companies (Wang et al, 2014a ). In this work, we investigated six artificial cultivated bases and two individual cultivated plantations (Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies indicated that chemical constituents of BFC mainly include steroidal alkaloids, saponins, terpenoids, and glycosides (Hao et al, 2013 ). It is believed that alkaloids are the major biological active constituents (Li et al, 2013 ; Wang et al, 2014a ). Recent pharmacological studies found that alkaloids from BFC exhibit remarkable antitussive, expectorant, anti-inflammatory effects (Wang et al, 2011 , 2012 ), antiasthmatic effect (Yan, 2005 ), hypotensive property (Kang et al, 2004 ), anti-bacterial activity (Li et al, 2005 ), and antitumor effect (Wang D. D. et al, 2014 ; Wang et al, 2014b , 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So, the CE was subjected to further purification to get total alkaloids of BFU (TAFU). TAFU was prepared by using previous methods [ 15 ]. Simply, the CE was dissolved and chromatographed over H-103 resin column, which was eluted with distilled water, 10% alcohol and 90% ethanol, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…As the fundamental components of FCB, alkaloids are traditionally believed to be responsible for the pharmacological activities of FCB [ 34 ] and have been considered as a key index for the identification and quality control of FCB [ 36 ]. Interestingly, the content of total alkaloids in FCB is extremely low, approximately ranging from 0.02% to 0.3% [ 40 ]. Previous studies showed that the alkaloids from FCB could be classified into two groups based on the carbon framework: isosteroidal alkaloids and steroidal alkaloids; the former accounts for approximately 75% of the total alkaloids [ 18 , 41 ].…”
Section: Phytochemistrymentioning
confidence: 99%